Can’t see the forest for the trees: The influence of marker type on inferred phylogenetic relationships in a cosmopolitan bat genus - Thomas M. Lilley; Veronika N. Laine; Fernanda Ito dos Santos; Flora Whiting-Fawcett; Diego S. Porto; Aída Otálora-Ardila; Enrico Bernard; Michael Buchalski; Devaughn Fraser; Joseph Hoyt; Joseph Johnson; Kuniko Kawai; et al. (Molecular Phylogenetics and Evolution, 2026)

Host gene expression in wildlife disease: making sense of species‐level responses - Evan A. Eskew; Devaughn Fraser; Maarten J. Vonhof; Malin L. Pinsky; Brooke Maslo (Molecular Ecology, 2021)
Emerging infectious diseases are significant threats to wildlife conservation, yet the impacts of pathogen exposure and infection can vary widely among host species. As such, conservation biologists and disease ecologists have increasingly aimed to understand species‐specific host susceptibility using molecular methods. In particular, comparative gene expression assays have been used to contrast the transcriptomic responses of disease‐resistant and disease‐susceptible hosts to pathogen exposure. This work usually assumes that the gene expression responses of disease‐resistant species will reveal the activation of molecular pathways contributing to host defence. However, results often show that disease‐resistant hosts undergo little gene expression change following pathogen challenge. Here, we discuss the mechanistic implications of these “null” findings and offer methodological suggestions for future molecular studies of wildlife disease. First, we highlight that muted transcriptomic responses with minimal immune system recruitment may indeed be protective for nonsusceptible hosts if they limit immunopathology and promote pathogen tolerance in systems where susceptible hosts suffer from genetic dysregulation. Second, we argue that overly narrow investigation of responses to pathogen exposure may overlook important, constitutively active molecular pathways that underlie species‐specific defences. Finally, we outline alternative study designs and approaches that complement interspecific transcriptomic comparisons, including intraspecific gene expression studies and genomic methods to detect signatures of selection. Collectively, these insights will help ecologists extract maximal information from conservation‐relevant transcriptomic data sets, leading to a deeper understanding of host defences and, ultimately, the implementation of successful conservation interventions.

Genome‐wide expression reveals multiple systemic effects associated with detection of anticoagulant poisons in bobcats ( Lynx rufus ) - Devaughn Fraser; Alice Mouton; Laurel E. K. Serieys; Steve Cole; Scott Carver; Sue Vandewoude; Michael Lappin; Seth P.D. Riley; Robert Wayne (Molecular Ecology, 2018)
Anticoagulant rodenticides ( AR s) are indiscriminate toxicants that threaten nontarget predatory and scavenger species through secondary poisoning. Accumulating evidence suggests that AR exposure may have disruptive sublethal consequences on individuals that can affect fitness. We evaluated AR ‐related effects on genome‐wide expression patterns in a population of bobcats in southern California. We identify differential expression of genes involved in xenobiotic metabolism, endoplasmic reticulum stress response, epithelial integrity and both adaptive and innate immune function. Further, we find that differential expression of immune‐related genes may be attributable to AR ‐related effects on leucocyte differentiation. Collectively, our results provide an unprecedented understanding of the sublethal effects of AR exposure on a wild carnivore. These findings highlight potential detrimental effects of AR s on a wide variety of species worldwide that may consume poisoned rodents and indicate the need to investigate gene expression effects of other toxicants added to natural environments by humans.